Experimental evidence of an acetate transporter protein and characterization of acetate activation in aceticlastic methanogenesis of Methanosarcina mazei. Issue 2 (28th August 2014) - Welte, Cornelia; Kröninger, Lena; Deppenmeier, Uwe
Abstract Aceticlastic methanogens metabolize acetate to methane and carbon dioxide. The central metabolism and the electron transport chains of these organisms have already been investigated. However, no particular attention has been paid to the mechanism by which acetate enters the archaeal cell. In our study we investigated Methanosarcina mazei acetate kinase (Ack) and the acetate uptake reaction. At a concentration of 2 mM acetate, the Ack activity in cell extract of M. mazei was not limiting for the methane formation rate. Instead, the methanogenesis rate was controlled by the substrate concentration and increased 10‐fold at 10 mM acetate. Subsequently, we analyzed the involvement of the putative acetate permease MM_0903 using a corresponding deletion mutant. At 2 mM acetate, only 25% of the wild‐type methane formation rate was measured in the mutant. This indicated that the supply of acetate to Ack was limiting the rate of methane formation. Moreover, the mutant revealed an increased acetate kinase activity compared with the wild type. These results show for the first time that an acetate transporter is involved in aceticlastic methanogenesis and may be an important factor in the acetate threshold concentration for methanogenesis of Methanosarcina spp.